2020
DOI: 10.1021/acsanm.0c00103
|View full text |Cite
|
Sign up to set email alerts
|

Poly(p-xylylene) Nanotubes Decorated with Nonagglomerated Gold Nanoparticles for the Alcoholysis of Dimethylphenylsilane

Abstract: Nanoparticles immobilized on protective polymer supports are highly attractive for various applications in industrial processes. However, nanoparticles tend to agglomerate during the preparation of the polymer supports because of often used harsh conditions and thus lose their specific functionalities, like the catalytic active surface. Here, we report a method that solves the agglomeration and loss of activity by a sacrificial intermediate polylactide (PLA)/gold nanoparticle (AuNP) composite material that was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…The resulting patchy nonwovens were loaded with gold NPs through a simple dip-coating process ( Figure 11 c), which was driven by a ligand exchange reaction. The hybrid nonwovens were successfully applied as catalysts for the alcoholysis of dimethylphenylsilane ( Figure 11 d) at room temperature, showing a comparable or even higher catalytic activity than other supports reported before [ 188 , 189 , 190 , 191 , 192 , 193 ]. Moreover, the employed patchy hybrid nonwovens were easily recoverable from the reaction medium and reusable in at least 10 consecutive catalysis cycles.…”
Section: Properties and Applicationsmentioning
confidence: 63%
“…The resulting patchy nonwovens were loaded with gold NPs through a simple dip-coating process ( Figure 11 c), which was driven by a ligand exchange reaction. The hybrid nonwovens were successfully applied as catalysts for the alcoholysis of dimethylphenylsilane ( Figure 11 d) at room temperature, showing a comparable or even higher catalytic activity than other supports reported before [ 188 , 189 , 190 , 191 , 192 , 193 ]. Moreover, the employed patchy hybrid nonwovens were easily recoverable from the reaction medium and reusable in at least 10 consecutive catalysis cycles.…”
Section: Properties and Applicationsmentioning
confidence: 63%
“…The resulting patchy nonwovens were loaded with gold NPs through a simple dip-coating process (Figure 11c), which was driven by a ligand exchange reaction. The hybrid nonwovens were successfully applied as catalysts for the alcoholysis of dimethylphenylsilane (Figure 11d) at room temperature, showing a comparable or even higher catalytic activity than other supports reported before [188][189][190][191][192][193]. Moreover, the employed patchy hybrid nonwovens were easily recoverable from the reaction medium and reusable in at least 10 consecutive catalysis cycles.…”
Section: Heterogeneous Catalysismentioning
confidence: 69%
“…To ensure high catalytic reaction rates, AuNPs should have, in general, a very high surface area. However, because of insufficient stabilization, AuNPs often tend to agglomerate to reduce their surface energy . To circumvent agglomeration, AuNPs are usually stabilized by colloidal ligands or immobilized on the surface of support materials such as polymers or metal–organic frameworks. Different research groups have used electrospun polymer nonwovens as a support to immobilize AuNPs and demonstrated their applicability for different catalytic reactions. For instance, Liu et al showed the preparation of gold/polyacrylonitrile (Au/PAN) electrospun nonwovens for the 4-nitrophenol reduction combining electrospinning, amination, and the electroless plating technique. Efficient immobilization of AuNPs on the electrospun PAN fibers was achieved by introducing amine and imide groups onto the fibers’ surface .…”
Section: Introductionmentioning
confidence: 99%
“…Another approach was reported by our group, who developed tea-bag-type carriers based on electrospun polymer fibers and nanotubes for the efficient immobilization of AuNPs. We demonstrated that these systems can be beneficial being used and reused for catalytic alcoholysis. ,, In this kind of system, leaching of the catalyst is still an unresolved issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation